(untitled) (Ameghiniana, 2014)
Bibimys cf. B. torresi Massoia, 1979 and Pseudoryzomys aff. P. simplex (Winge, 1887) are mentioned for first time from the late Holocene of Argentina. Several remains of this species were found in the upper levels of archaeological site Cueva Tixi (General Alvarado County, Buenos Aires Province). Both records are located south of the present areas of distribution of those species. The paleoenvironmental significance of the cricetid assemblage studied is discussed and suggest that temperature and humidity conditions were more benign in the upper Holocene than in the early-middle Holocene.